Functional analysis of NK cell subsets activated by 721.221 and K562 HLA‐null cells - Lisovsky, Irene; Isitman, Gamze; Bruneau, Julie; Bernard, Nicole F. (Journal of leukocyte biology, 2015)
Higher frequency 721 stimulated NK cells secrete IFN‐γ and/or CCL4, while CD107a expression dominates the response to K562. HLA‐null cell lines [721.221 (henceforth, 721) and K562] are often used to study NK cell activation. NK cells are innate immune lymphocytes that express a variety of stochastically expressed inhibitory and activating receptors. Although it is known that 721 and K562 have divergent origins, they have been used interchangeably to stimulate NK cells in many studies. We hypothesized that the differences between 721 and K562 cells may result in differential NK cell‐activation patterns. In this report, we assessed all possible combinations of CD107a expression and IFN‐γ and CCL4 secretion in total NK and 3DL1+/− NK cell populations induced by these 2 cell lines. 721 activates a significantly higher frequency of NK cells and 3DL1+ NK cells than K562. The NK cell functional subsets that are stimulated to a higher degree by 721 than K562 include those secreting IFN‐γ and/or CCL4. On the other hand, the functional subsets that include CD107 expression contribute to a higher proportion of the total NK cell response following stimulation with K562 than 721. These results have implications for the selection of HLA‐null cell lines to use as NK cell stimuli in investigations of their role in infectious diseases, cancer, and transplantation.